PENGARUH PENGGUNAAN SCREEN TIME TERHADAP SPEECH DELAY PADA BALITA: KAJIAN LITERATUR - Adelia Anggretha Malau; Sipriana Anggi M. Br Simanjorang; Veronika Sitanggang; Evanny Indah Manurung; Ester Silitonga (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2023)
Screen time is the exposure time to digital media such as television, video games, and other technologies that use digital screens. During the COVID-19 pandemic, screen time in toddlers has increased so much that it affects the process of toddler development. One of the social development disorders due to screen time is speech delay. Speech delay is a delay in speech ability that is not appropriate for the age of a toddler. This study aims to identify the effect of screen time on speech delay in toddlers based on a literature review. The method used is thematic analysis: a simplified approach by searching articles using the EBSCO, CORE, PubMed, and PMC databases. Articles were selected using the PRISMA flow chart and the JBI Critical Appraisal Checklist for Analytical Cross-Sectional Studies to analyse the quality of the articles. Researchers use the boolean operators